2014
DOI: 10.11152/mu.201.3.2066.164.1mat
|View full text |Cite
|
Sign up to set email alerts
|

The use of real-time elastography in the assessment of gallbladder polyps: preliminary observations

Abstract: Aims: Gallbladder polyps often have a benign nature. Current guidelines suggest surgical removal of polyps greater than 10 mm. However, the accuracy of the size criteria is limited because neoplasia can be found in gallbladder polyps less than 10 mm. The aim of this study was to evaluate the feasibility of real time elastography for gallbladder polyps and to demonstrate the elasticity properties of the polyps. Material and method: Fifty-three polypoid lesions of the gallbladder were prospectively examined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In addition, new elastographic technology, which is increasingly emerging [35,36], may contribute in the future to settle these doubts, as has been reported by some preliminary observations [37].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, new elastographic technology, which is increasingly emerging [35,36], may contribute in the future to settle these doubts, as has been reported by some preliminary observations [37].…”
Section: Discussionmentioning
confidence: 96%
“…Real-time elastography is a dynamic technique that objectively assesses the elastic properties of tissues by measuring the degree of deformation under the action of external forces. Teber et al [ 75 ] initially assessed that real-time elastography is feasible in the diagnosis of GPLs and benign lesions with high-strain elastography patterns. However, there are few studies and clinical applications of elastography, and more clinical studies are needed to understand the effectiveness of this technology in diagnosing GPLs.…”
Section: Diagnosismentioning
confidence: 99%
“…US-E could be an additional tool to distinguish malignancies from benign condition of gallbladder wall. Using SE, gallbladder polyps were characterized by medium-high strain (soft or moderately soft) compared to only one single small nodule (measuring 19 mm) defined as gallbladder carcinoma which exhibited low strain (high stiffness) [ 83 ]. Considering differential diagnosis between benign wall thickening and gallbladder carcinoma, Kapoor et al, reported that the p-SWE values could distinguish between the two conditions with 92.8% accuracy [ 84 ].…”
Section: Gallbladdermentioning
confidence: 99%